Installation of embedded generation using sensitivity index for loss minimization in power system / Hartini Jusoh @ Talib - Jusoh @ Talib, Hartini (2016)
This paper presents an alternative method of solving loss minimization in power system using sensitivity index (SI). Newton-Rhapson method is used for load flow calculation to determine the power flow and losses in each lines.